Pakistan at the Threshold of the 21st Century: How to Shape a Better Economic Future? (The Mahbub ul Haq Memorial Lecture) (The Pakistan Development Review, 1998)
Pakistan has been facing a deep-seated economic and financial crisis and seemingly intractable governance issues for the last few years. Factors such as international sanctions and global economic slowdown, which have worsened Pakistan’s economic difficulties, were beyond Pakistan’s control. But by and large, the country’s economic and financial difficulties are the result of economic mismanagement in key areas over long periods. Bad governance, as reflected in widespread corruption and poor delivery of public services, and especially poor law and order have given birth to a crisis of confidence in the state. It is argued here that despite this scenario, a long and arduous process of building institutions, setting the policies right, and enforcing a rule-based governance stressing both merit and accountability can put Pakistan back on the road to shared prosperity. Resolving financial problems, accelerating demographic transition, exploiting tremendous agricultural potential, improving both availability and quality of education, increasing competitiveness and bringing about structural change in exports and industry, and reforming the government are crucial policy actions that can help shape a better future for the country and end the economic drift.